Intermediate and Severe Hyperhomocysteinemia with Thrombosis: A Study of Genetic Determinants - Gaustadnes, Mette; Rüdiger, Niels; Rasmussen, Karsten; Ingerslev, Jørgen (Thrombosis and Haemostasis, 2000)
Hyperhomocysteinemia is an independent risk factor for cardiovascular disease. In search of genetic factors causing elevated levels of total homocysteine in plasma (tHcy), we investigated a cohort of consecutively identified, unrelated thrombosis patients (n = 28) having intermediate or severe hyperhomocysteinemia (30 µmol/l<tHcy ≤100 µmol/l, and tHcy >100 µmol/l, respectively). The methylenetetrahydrofolate reductase (MTHFR) 677C→T genotype, and the complete cystathionine β-synthase (CBS) genotype was determined in all patients. We found that the MTHFR T/T genotype was strongly correlated with intermediate hyperhomocysteinemia, being present in 73.9 % of those cases (17 of 23). In three of five patients with severe hyperhomocysteinemia, compound heterozygosity for CBS mutations was detected. Among the mutations, two novel missense mutations: 1265C→T (S422L) and 1397C→T (S466L) were detected. The phenotype in those patients was quite mild, thromboembolism apart. This indicates that a search for CBS mutations in patients with severe hyperhomocysteinemia is important to ensure the detection of a possible CBS deficiency, thus enabling treatment. Co-existence of the MTHFR T/T genotype and the common CBS 844ins68 variant was significantly higher among patients (10.7%) as compared to controls (1.2%), indicating that this genotype combination is a thrombotic risk factor (P <0.05). In a few patients, hyperhomocysteinemia could not be explained by this genetic approach, suggesting that other genetic risk factors were implicated.Abbreviations: MTHFR, methylenetetrahydrofolate reductase; CBS, cystathionine β-synthase; tHcy, total homocysteine in plasma.
Keywords: Homocysteine; hyperhomocysteinemia; intermediate-; severe-; cystathionine β-synthase deficiency; MTHFR 677C→T polymorphism; venous thrombosis; stroke